Investigating long-run stock returns after corporate events : the UK evidence - Dutta, Anupam (Virtus Interpress, 2014)
The objective of this paper is to assess the robustness of the existing long-run event study methodologies in the UK stock market. In doing so, the study employs the buy-and-hold abnormal return approach and the calendar time portfolio method to identify the long-term abnormal performance following corporate events. Although many recent studies consider the application of these two widely used approaches, each of the methods is a subject to criticisms. This paper uses the standardized calendar time approach (SCTA) which presents a number of important improvements over the traditional calendar time methodology. The empirical analysis reveals that all the traditional methodologies perform well in the UK security market. Our findings further report that SCTA documents better specification and power than the conventional approaches.
Keywords: long-run anomalies; standardized abnormal returns; specification issue; power issue; security market; yield; mathematical models; prices; shares; stock prices; effects (results); water analysis; reliability (general); laboratories; Tilastotiede